2007
DOI: 10.1080/08820130601069731
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Serum IgA Level and Cartilage Erosion in 436 Cases of Rheumatoid Arthritis

Abstract: More patients with X-ray grading as cartilage erosion (slight, medium or severe) showed abnormal IgA comparing to those in X-ray grading as normal (p<0.05-0.01) both in preliminary investigation and after 6 months' follow-up. The serum IgA level in RA with X-ray grading as slight, medium or severe cartilage erosion was elevated remarkably comparing with in grading as normal (p<0.05-0.01). The Spearman Analysis showed that the level of serum IgA presents positive correlation with X-ray grading both in prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…The involvement of IgA RF in extra‐articular manifestations in RA was also reported . In a large patient cohort study, a positive correlation was found between the increase in serum IgA and the grade of cartilage destruction in active RA . Furthermore, clinical studies showed that anti‐TNF‐α treatment of RA patients reduced IgM, IgG, and IgA RF levels.…”
Section: Targeting Fcαri In Diseasementioning
confidence: 83%
See 1 more Smart Citation
“…The involvement of IgA RF in extra‐articular manifestations in RA was also reported . In a large patient cohort study, a positive correlation was found between the increase in serum IgA and the grade of cartilage destruction in active RA . Furthermore, clinical studies showed that anti‐TNF‐α treatment of RA patients reduced IgM, IgG, and IgA RF levels.…”
Section: Targeting Fcαri In Diseasementioning
confidence: 83%
“…Interestingly, several studies reported a correlation between the presence of IgA RF or IgA ACPA in blood or synovial fluid and worse disease prognosis as well as severe bone erosions . This raises the hypothesis that IgA can contribute to pathology, as cross‐linking of FcαRI by immune complexes triggers neutrophil‐induced inflammation.…”
Section: Targeting Fcαri In Diseasementioning
confidence: 99%
“…It was demonstrated that IgA1 immune complexes contain soluble FcaRI, which may block the binding between IgA and membrane-bound FcaRI [37,38], which could explain why neutrophils are not activated in IgA nephropathy. Patients with rheumatoid arthritis have IgA autoantibodies against the Fc domain of IgG (rheumatoid factor, RF), and a correlation between IgA RF and worse disease prognosis as well as severe bone erosion has been reported [39,40]. As the synovial fluid of patients with RA contains high numbers of neutrophils, it is conceivable that neutrophils induce inflammatory responses via FcaRI, ultimately leading to destruction of joint tissue.…”
Section: Iga and Autoimmune Diseasesmentioning
confidence: 99%
“…Thus it is reasonable to make the hypothesis that there is a positive correlation among IgA (reflecting immune response), platelet and cartilage erosion (severe in late stage) in RA. The changes in peripheral IgA level and platelet number positively correlated with the grade of cartilage damage in active RA patients, thus supporting the hypothesis (Zha et al, 2006;He et al, 2007b). In the clinical practice, the CMMs with activating blood stasis pattern, and those reinforcing deficiency pattern and containing polysacharides or animal proteins were used for the treatment (Yang et al, 2003;Zhang et al, 2010).…”
Section: Tcm Pattern Classification Could Lead New Findings In Biomedmentioning
confidence: 75%